The association of distress and denial of responsibility with maladaptive personality traits and self-esteem in offenders - Xuereb, Sharon (Legal and criminological psychology, 2015)
This study aimed to examine the relationship of offenders' distress and responsibility with maladaptive personality traits, self-esteem, and offence-type. It also further validated the Distress and Responsibility Scale (DRS; Xuereb et al., 2009a, Pers. Individ. Diff., 46, 465). A new sub-scale measuring social desirability was included and assessed in the DRS. Maladaptive personality traits and self-esteem were measured in relation to the following predictions: (1) that maladaptive personality traits would positively correlate with distress (2) that self-esteem would negatively correlate with distress and acknowledging responsibility. The sample was 405 male sexual, violent, and general offenders from a UK prison. Participants anonymously completed a questionnaire measuring the variables under investigation. The factor-structure of the DRS was confirmed via Confirmatory Factor Analysis after minor changes. No significant differences in distress and denial of responsibility were found between sexual, violent, and general offenders. Maladaptive personality traits positively correlated with chronic and offence-related distress, chronic self-blame, and minimization of offence harm. Chronic and offence-related distress and responsibility negatively related to self-esteem. The study concludes that the DRS has reached stability, and that the social desirability scale increases the measure's validity. Assessment and treatment for offence-related distress and denial of responsibility should be offered to all offence groups. Offenders would benefit from structured interventions to manage difficulties associated with maladaptive personality traits, including chronic distress and self-blame. Finally, it was concluded that self-esteem might serve a self-defensive function for offenders.